The Effectiveness of the Muhadatsah Method in Improving the Maharah Kalam of Students at MTs Al-Ishlah Tanjung Jabung Timur - Khairul Fajri; M. Syukron Maksum (Universitas Muhammadiyah Enrekang, 2026)
This study aims to analyze the effectiveness of the muhadatsah method in improving students' speaking skills (maharah kalam) in Arabic learning at MTs Al-Ishlah Tanjung Jabung Timur. The background of this study is based on the low Arabic speaking ability of students caused by the dominance of conventional learning methods oriented toward grammar memorization and translation. This research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The population consisted of all eighth-grade students of MTs Al-Ishlah, with a sample of 60 students divided into experimental and control classes. Data collection techniques included oral tests, observation, documentation, and supporting interviews. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the t-test. The results showed that the average posttest score of the experimental class was 82.4, higher than the control class score of 71.6. The t-test result showed a significance value of 0.000 < 0.05, indicating that the muhadatsah method significantly affected students' speaking skill improvement. The novelty of this study lies in the implementation of context-based muhadatsah using students' daily life situations in rural madrasah settings, which has not been widely discussed in previous studies. This study recommends the systematic use of the muhadatsah method in Arabic language learning at the junior Islamic school level.